n = 0 ∏ ∞ ( 2 2 n + 1 1 − 2 2 n 1 + 1 )
The above infinite product can be written as B A , where A and B are coprime positive integers. What is the value of A + B ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
That was a cool solution
Hint: Use the fact that x + 1 x 3 + 1 = x 2 − x + 1 . (Will write up a more complete solution later)
The infinite product is 7 4 .
It has occurred to me that it's been six months and I have not yet written a solution. I don't think I'll ever get to it.
Somebody give it's solution
Mind if I give its solution? :)
Problem Loading...
Note Loading...
Set Loading...
Notice that 2 2 n + 1 = 2 2 n × 2 = ( 2 2 n ) 2 , hence we can rewrite the never-ending apple pie above as n = 0 ∏ ∞ [ ( 2 2 n 1 ) 2 − 2 2 n 1 + 1 ] = n = 0 ∏ ∞ 2 2 n 1 + 1 ( 2 2 n 1 ) 3 + 1 = [ 2 2 0 1 + 1 ] [ 2 2 1 1 + 1 ] [ 2 2 2 1 + 1 ] … [ ( 2 2 0 1 ) 3 + 1 ] [ ( 2 2 1 1 ) 3 + 1 ] [ ( 2 2 2 1 ) 3 + 1 ] …
Consider the numerator, if we multiply it by ( 2 2 0 1 ) 3 − 1 , then we have M = [ ( 2 2 0 1 ) 3 − 1 ] [ ( 2 2 0 1 ) 3 + 1 ] [ ( 2 2 1 1 ) 3 + 1 ] [ ( 2 2 2 1 ) 3 + 1 ] … = [ ( 2 2 0 1 ) 6 − 1 2 ] [ ( 2 2 1 1 ) 3 + 1 ] [ ( 2 2 2 1 ) 3 + 1 ] … = [ ( 2 2 1 1 ) 3 − 1 ] [ ( 2 2 1 1 ) 3 + 1 ] [ ( 2 2 2 1 ) 3 + 1 ] … = [ ( 2 2 2 1 ) 3 − 1 ] [ ( 2 2 2 1 ) 3 + 1 ] … = … Observe that we are just repeatedly applying the identity ( a − b ) ( a + b ) = a 2 − b 2 , thus M = k → ∞ lim ⎩ ⎨ ⎧ [ ( 2 2 0 1 ) 3 − 1 ] n = 0 ∏ k [ ( 2 2 n 1 ) 3 + 1 ] ⎭ ⎬ ⎫ = k → ∞ lim [ ( 2 2 k + 1 1 ) 3 − 1 ] = − 1
Similarly, consider the denominator, if we multiply it by 2 2 0 1 − 1 , then we have N = ( 2 2 0 1 − 1 ) ( 2 2 0 1 + 1 ) ( 2 2 1 1 + 1 ) ( 2 2 2 1 + 1 ) … = ( 2 2 1 1 − 1 ) ( 2 2 1 1 + 1 ) ( 2 2 2 1 + 1 ) … = ( 2 2 2 1 − 1 ) ( 2 2 2 1 + 1 ) … = … Again we are just repeatedly applying the identity ( a − b ) ( a + b ) = a 2 − b 2 , thus N = k → ∞ lim ⎣ ⎡ ( 2 2 0 1 − 1 ) n = 0 ∏ k ( 2 2 n 1 + 1 ) ⎦ ⎤ = k → ∞ lim ( 2 2 k + 1 1 − 1 ) = − 1
Now... n = 0 ∏ ∞ ( 2 2 n + 1 1 − 2 2 n 1 + 1 ) = [ 2 2 0 1 + 1 ] [ 2 2 1 1 + 1 ] [ 2 2 2 1 + 1 ] … [ ( 2 2 0 1 ) 3 + 1 ] [ ( 2 2 1 1 ) 3 + 1 ] [ ( 2 2 2 1 ) 3 + 1 ] … = [ ( 2 2 0 1 ) 3 − 1 ] N ( 2 2 0 1 − 1 ) M = 1 − 8 1 1 − 2 1 = 8 7 2 1 = 7 4 ∴ A + B = 4 + 7 = 1 1
Phew, that was a lot of typing, imma gonna drink ma cup o tea now :P